Determination of Body Composition in Adolescense Using Body Mass Index and Bioelectric Impedance Analysis Methods - Özçelik, Oğuz; Çolak, Ramis; Ayan, Vedat; Aslan, Muammer (Fırat University, 2002)
Aim: To evaluate the validity of body mass index (BMI) and bioelectric impedance analysis (BIA) methods in determining body compositions in healthy male and female adolescenses. Materials and Methods: Body composition of 665 (359 male and 306 female) students, aged between 14-16 (mean±SD: 15.1±0.6 yr) were analysed using BMI and BIA methods. Results: Normal ranges for BMI (18.5-24.99 kg/m2) in male students for the ages 14, 15 and 16 years found to be: 51.02% (n=25), 65.46% (n=127) and 70.68% (n=82) respectively. However, normal values for body fat mass percents for the ages 14, 15 and 16 years were 22.44% (n=11), 19.94% (n=29) and 13.79% (n=16). In female students, normal ranges for BMI found to be %52.00 (n=26), %68.44 (n=141) and % 68.00 (n=34). However, normal values for body fat mass percents for the ages 14, 15 and 16 years were 28.00% (n=14), 34.46% (n=71) and 22.00% (n=11). Conclusion: In adolescense, BMI values may be insufficient method to analysis body composition. Thus BIA method should be considered to determine body composition especially in clinical evaluation.

Amaç: Adolesan dönemindeki sağlıklı gençlerde, beden kitle indeksi (BKİ) ve biyoelektrik impedans analiz (BIA) yöntemleri ile vücut kompozisyonlarının ölçülerek iki yöntemin etkinliklerinin karşılaştırılması. Gereç ve Yöntem: Çalışmada 14-16 yaş arasında (ortalama±SS: 15.1±0.6 yıl) olan, 665 (359 erkek, 306 kız) öğrencinin vücut kompozisyonları BKİ ve BIA yöntemleri ile ölçülerek değerlendirildi. Bulgular: Erkek öğrencilerde BKİ'lerine göre normal sınırlar (18.5-24.99 kg/m2) içinde olan dağılımları 14, 15 ve 16 yaşları için sırası ile: % 51.02 (n=25), % 65.46 (n=127) ve %70.68 (n=82) olarak bulundu. Vücut yağ yüzdelerine göre ise; %22.44 (n=11), %19.94 (n=29) ve %13.79 (n=16) normal yağ yüzdesine sahip grupta yer aldılar. Kız öğrencilerde ise BKİ'lerine göre %52.00 (n=26), %68.44 (n=141), ve % 68.00 (n=34) olarak bulundu. Vücut yağ yüzdelerine göre değerlendirilmesinde ise; %28.00, (n=14), %34.46 (n=71) ve % 22.00 (n=11) normal yağ yüzdesine sahip grupta yer aldılar. Sonuç: Adolesanlarda, BKİ kullanılması bireylerin vücut kompozisyonlarının değerlendirmede yetersiz kalmaktadır. Bu nedenle vücut kompozisyonunun belirlenmesinde BIA kullanılması değerlendirme açısından daha büyük önem taşımaktadır.
Adolesanların Vücut Bileşimlerinin Değerlendirilmesinde Vücut Kitle İndeksi ve Biyoelektrik İmpedans Analizinin Karşılaştırılması